6-3x=2x+9

Simple and best practice solution for 6-3x=2x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-3x=2x+9 equation:


Simplifying
6 + -3x = 2x + 9

Reorder the terms:
6 + -3x = 9 + 2x

Solving
6 + -3x = 9 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
6 + -3x + -2x = 9 + 2x + -2x

Combine like terms: -3x + -2x = -5x
6 + -5x = 9 + 2x + -2x

Combine like terms: 2x + -2x = 0
6 + -5x = 9 + 0
6 + -5x = 9

Add '-6' to each side of the equation.
6 + -6 + -5x = 9 + -6

Combine like terms: 6 + -6 = 0
0 + -5x = 9 + -6
-5x = 9 + -6

Combine like terms: 9 + -6 = 3
-5x = 3

Divide each side by '-5'.
x = -0.6

Simplifying
x = -0.6

See similar equations:

| 7=19-4m | | 2.5=-5n | | 7=10-4m | | 7(p+5)= | | (2*5)=180 | | X-2y=3x+4 | | 1.5x+19=2.27x+15 | | 34r+34=8(5r-1) | | 120=(n-2)180 | | x+111=79 | | -18=-9x | | 5+5=10+2 | | 1.5x+19=2.27+15 | | g-.75=-.6 | | 5(m)=67 | | 8m-5=-5-2m-m | | 3p-6=2q | | 50.45x+60=50.95 | | x^3+4x+80=0 | | -.07y-1.6=2.1y+1.2 | | 2x+3y=5x-2y+7 | | Kx(X-6)=2 | | .13x+X=20.34 | | 2.5r=120 | | 7.7a+11=72.6 | | 7+55x=33x+19 | | 5+5=2 | | (.2y)*y=.45 | | -8h+2h-10=-28 | | 3.5(-83x-3)=3.7(7x-30) | | 2x=3x-23 | | y=-16x^2+12x+0.2 |

Equations solver categories